POTRET KESEJAHTERAAN RAKYAT DI PROVINSI BALI MENGGUNAKAN METODE CHERNOFF FACES - DIRGANTARA, I WAYAN WIDHI; SUKARSA, KOMANG GDE; DHARMAWAN, KOMANG (E-Jurnal Matematika, 2013)
Chernoff Faces method is a graphical method of visualization techniques to present data with many variables in the form of a cartoon face which can be determined by 20 parameters or less . In this research it was shown how the Chernoff Faces method was used to see welfare of the people in the province of Bali and Bali's nine regencies . To pair the variables and Chernoff’s facial features, then we used  Principal Component Analysis and survey to make the faces look more human . The result f rom 18 indicators of welfare of the people in the province of Bali, only 8 indicators were not really well. It was obtained too that Tabanan was the most prosperous regency and Karangasem was the les t prosperous regency.
Keywords: Welfare of The People; Principal Component Analysis; Chernoff Faces